Comparative study of Article 10 Letter C of Law of The Republic of Indonesia Number 8 Year 1999 concerning Consumer Protection and sharia business law in online clothing sales - Kusnalia, Linda; Islami, Trinah Asi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This article discusses the problems faced by buyers in online buying and selling, in the form of advertisements that do not match the products being sold. For this reason, researchers are interested in conducting research with the title Comparative Study of Article 10 Letter C of Law Number 8 of 1999 concerning Consumer Protection and Sharia Business Law in Online Clothes Buying and Selling by examining three online shops, namely Sa**tri.Store 1**6611424, N**la.Fasshion, and Ocyd Clothing Official. Methods: The research method uses empirical juridical, with a phenomenological and conceptual approach. Data analysis uses inductive and descriptive methods. The data collection techniques used were observation, interviews, documentation, questionnaires and library data. Findings: The results of the research show that the two online stores studied, namely Sa**tri.Store 1**6611424, and N**la.Fasshion are known to have committed fraud with advertising media that is misleading and contains elements of gharar and jahalah. Conclusion: Meanwhile, the Ocyd Clothing Official online shop is known to comply with applicable regulations, both from the Consumer Protection Law and Sharia Business Law. Novelty/Originality of this Study: Its comparative analysis of Article 10, Letter C of Law Number 8 of 1999 on Consumer Protection with Sharia Business Law, specifically within the context of online clothing sales, provides a unique examination of legal and ethical perspectives. This approach highlights the differences and commonalities in addressing false advertising in Indonesia's burgeoning e-commerce sector.